Optically stimulated luminescence of amorphous/microcrystalline SiO2 (silex): basic investigations and potential in archeological dosimetry - Schmidt, Christoph; Kreutzer, Sebastian (Quaternary geochronology, 2013)
Unlike the well-studied optically stimulated luminescence (OSL) signal of (macrocrystalline) quartz, not much is known about OSL from natural amorphous and microcrystalline silicon dioxide. These materials - generally termed “silex” - were widely used for prehistoric tool production, and thermoluminescence (TL) is routinely applied do date the firing event of heated specimens. This study presents data on basic OSL characteristics of silex such as signal composition and component-resolved thermal stability as well as the applicability of OSL for dating of burnt lithic tools. Fitting of LM-OSL curves yielded similar components (mostly five) as observed for quartz, with the photoionization cross-sections being in the same order of magnitude for both materials. Three different methods (LM-OSL pulse annealing, short-shine pulse annealing as well as the varying heating rate method) were applied to study the thermal stability of components and allowed calculating trap parameters E and s, and hence the electron retention lifetime. Only the most light-sensitive (“fast-like”) component proved to be of sufficient thermal stability for dating applications, as evidenced from coherent experimental results. All other components already diminished at preheating temperatures > 200 °C. Pulse annealing measurements further indicate that electron populations sampled by OSL and those responsible for the ca. 380 °C TL-“dating peak” are not identical. Dose recovery tests applying an OSL-SAR protocol with “hot bleach” in between the regeneration cycles showed good reproducibility of a known dose if only the initial OSL signal (ca. 0-0.5 s at 90% LED power) is used. Finally, obtained OSL-SAR and TL ages based on the blue TL emission are in agreement within errors for two Middle Paleolithic archeological samples showing a “fast-like” component. These results verify the experimental findings of sufficient long-term stability of the initial OSL signal. Since not all silex specimens deliver a bright and stable OSL signal, optical ages of suitable samples may serve as an additional internal check for the paleodose estimate rather than substituting TL as a standard technique for dating of heated silex.
Im Titel ist 2 bei SiO2 tiefgestellt
Online verfügbar: 30. Januar 2013
Gesehen am 31.03.2025